Inventory of Macroscopic Fungi in Regional Watersheds Bukit Barisan I Protected Forest, Lubuk Paraku, Lubuk Kilangan District, Padang City - Ocstavella, Nadya; Handayani, Dezi (Microbiotech, 2024)
Indonesia is a tropical country that is rich in biodiversity. One of these biodiversity is mushrooms. Based on their size, fungi are divided into two, namely microscopic and macroscopic fungi. Macroscopic fungi are often found in the rainy season, especially in dead or rotting wood, leaf litter and in damp places. This research was carried out from September 2023 to January 2024 in the Bukit Barisan I Protected Forest Area, Lubuk Paraku, Lubuk Kilangan District, Padang City. The method used for inventory is a survey by exploring the research location and taking samples incidentally. Fungal samples of each type found were collected and then taken to the Biology Laboratory for identification using the Collins Fungi Guide reference book and related scientific articles. Information regarding the diversity of macroscopic fungi in this area has never been reported, so researchers conducted research in this area. There were 13 types of macroscopic fungi found in this study consisting of 1 division, 4 orders, 7 families, 10 genera and 13 species. The identification results show that the mushrooms are Ganoderma sp 1., Ganoderma sp 2., Trametes ochracea, Earliella sabrosa, Microporus affinis, Pluteus sp 1., Pluteus sp 2., Coprinellus sp., Coprinellus disseminatus, Schizophyllum sp., Inocybe sp. , Phylloporus sp., Lactarius sp.